Analiz dissertacij v oblasti sporta vysšich dostiženij i podgotovki sportivnogo rezerva - Baranov, V. N.; Shustin, B. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
In the total amount of dissertation research in the field of physical culture and sports in our country, work in the field of sports training occupies the greatest place. They include the training of elite athletes and the preparation of a sports reserve, both in general and in individual sports. This article presents the results of a comparative analysis of dissertations on the main directions of scientific research in sports in the Russian Federation in 1991-2016. At that, such sections as initial training, training of elite athletes, medical and biological support of sports training, psychological support, biomechanics of sports, sports pedagogy, adaptive sports, refereeing, history of sports are highlighted. The dynamics of the preparation of dissertations on the main groups of sports in 2008-2016 is given. Distribution of sports-oriented dissertations by main pedagogical specialties and other branches of science in 1991-2016 is revealed